Axisymmetric Hybrid Nanofluid Flow Due to a Convectively Heated Stretching/Shrinking Disk - Najiyah Safwa, Khashi'ie; Iskandar, Waini; Pop, Ioan; Nurul Amira, Zainal; Abdul Rahman, Mohd Kasim (Akademi Baru, 2021)
This significant study is designed to analyze the axisymmetric hybrid nanofluid flow with heat transfer on a convectively heated stretching/shrinking disk. The combination of metal (Cu) and metal oxide (Al2O3) nanoparticles with water (H2O) as the base fluid is used for the analysis. Similarity transformation is adopted to reduce the complexity of the PDEs into a system of ODEs. The utilization of suction in maintaining the steady flow solution for the shrinking disk case discloses the presence of dual solutions. Besides, an upsurge of Biot number and suction’s strength enhances the heat transfer operation. The application of Cu-Al2O3/water nanofluid can extend the range of solutions’ existence and consequently, decelerate the separation of laminar flow.